BRASIL ILUSTRADO (1877-1878) AND FELIX FERREIRA: USEFUL KNOWLEDGE ON BEHALF OF THE NATION - Luca, Tania Regina de [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2020)
The article analyzes the periodical Brasil Ilustrado: arquivo de conhecimentos uteis, released in Rio de Janeiro in January 1887. In addition to establish its place among the many illustrated publications that emerged throughout the nineteenth century, we intend to identify its nature, its editorial project, the reasons that motivated its owners to take forward the idea and analyze its textual and iconographic content. Particular attention is given to Felix Ferreira, who was effectively responsible for the journal's direction. At the same time, readers in Brazil had the opportunity to acquire another monthly journal, A Ilustracao (1884-1892), printed in Paris and regularly arriving in Lisbon and Rio de Janeiro from the harbor of Bordeaux. The confrontation of the two periodicals invites us to reflect on the printing conditions in the capital of the Empire, at a time when it was urgent to obtain inexpensive, fast and efficient methods of reproduction of visual information, whose demand grew in a very significant way during the nineteenth century.
Keywords: Illustrated press; Brasil Ilustrado; Felix Ferreira; wood engraving; A Ilustracao